Manajemen Perpustakaan Sekolah/Madrasah: Strategi, Tantangan, dan Implementasi Teknologi - Irwansyah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Library management is a crucial aspect to ensure efficient and effective access to information resources for users. It involves planning, organizing, directing, and controlling the library's information resources, including collections, staff, budget, and information technology. The main objective of library management is to support and enhance learning, research, and knowledge development by providing high-quality and relevant information services. The principles of library management include planning, organizing, leadership, control, collection development, user services, and technology utilization. Libraries play a significant role in supporting the learning process in schools and madrasas by providing various learning resources, facilitating independent learning, enhancing information literacy, supporting student research and projects, promoting a reading culture, collaborating with teachers, providing access to digital resources, and offering reference and consultation services. Collection development is a critical aspect of library management, involving the systematic selection and acquisition of library materials based on user needs, curriculum relevance, and the latest developments in various fields of knowledge. The maintenance and preservation of library collections are also essential to ensure their longevity and accessibility. Effective library management strategies, including the development, maintenance, and preservation of collections, are vital to providing diverse and high-quality resources that support learning, research, and knowledge development in educational environments.